Anti-MHC autoimmunity in Behcet's disease: T cell responses to an HLA-B-derived peptide cross-reactive with retinal-S antigen in patients with uveitis - DİRESKENELİ, RAFİ HANER (BLACKWELL SCIENCE LTD, 2001)
Immune response to retinal autoantigens plays a central role in the pathogenesis of uveitis. A synthetic peptide (B27PD) from a common sequence of various HLA-B molecules associated with uveitis, such as HLA-B27 and 51, which shares amino acid homologies with a retinal-S antigen (S-Ag)-derived peptide (PDSAg), was shown to be immunogenic in human and experimental uveitis in the rat. In this study we investigated T cell responses to B27PD and PDSAg in patients with Behcet's disease and posterior uveitis (BD-posterior uveitis; n = 33) in comparison with non-Behcet anterior uveitis (AU, n = 14), Behcet's patients without uveitis (BD, n = 15) and healthy controls (HC, n = 32) in a 6-day proliferation assay. Patients with BD and posterior uveitis had significantly higher responses (stimulation index (SI) 2.8 +/- 1.3) than those with AU (SI 1.5 +/- 0.4), BD without uveitis (SI 1.1 +/- 0.4) and HC (SI 1.1 +/- 0.6) for B27PD (P < 0.0001). Responses to PDSAg were also higher in BD with posterior uveitis patients (SI 3.3 +/- 1.6) than AU (SI 1.5 +/- 0.4), BD without uveitis (SI 1.2 +/- 0.3) and HC (SI 1.1 +/- 0.6) (P < 0.0001). A significant correlation between the responses to PDSAg and B27PD (r = 0.56, P < 0.001) was observed. Elevated levels of IL-2 and tumour necrosis factor-alpha were also observed in culture supernatants obtained from peripheral blood mononuclear cells after stimulation with the peptides, but no correlation was found between the proliferative responses and cytokine levels. These results suggest that cellular immunity to cross-reactive HLA-B and S-Ag-derived peptides might play a role in the pathogenesis of posterior uveitis in BD.
Keywords: Behcet's disease; uveitis; retinal autoimmunity; HLA-B27; B51; NECROSIS-FACTOR-ALPHA; IMMUNOHISTOLOGY; RECEPTOR; TNF